2005
DOI: 10.1029/2004jb003394
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the deep lithospheric structure beneath the eastern margin of the Tibetan Plateau from gravity anomalies

Abstract: Various authors have investigated the mechanism of lateral support of the lithosphere in maintaining the uplift of the Tibetan Plateau, based on gravity data and elastic flexural modeling, in the south of the plateau across the Himalayas and in the north and the northwest across the Altyn Tagh and West Kunlun Shan. However, the degree of the regional compensation and lateral support to the east of the Tibetan Plateau has remained unknown. In this paper we present a lithospheric flexure model by interpreting gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 31 publications
2
43
1
1
Order By: Relevance
“…Gravity data across the Longmen Shan also suggest that little flexural loading of the Sichuan Basin occurred in Late Cenozoic time, and the crust here is (nearly) Airy-compensated ( Fig. 3; but see Jiang and Yu, 2005).…”
Section: Crustal Compensationmentioning
confidence: 85%
See 1 more Smart Citation
“…Gravity data across the Longmen Shan also suggest that little flexural loading of the Sichuan Basin occurred in Late Cenozoic time, and the crust here is (nearly) Airy-compensated ( Fig. 3; but see Jiang and Yu, 2005).…”
Section: Crustal Compensationmentioning
confidence: 85%
“…This older and computed (line) Bouguer gravity anomalies for Airy compensation of the Longmen Shan for a density contrast between crustal root and mantle of 400 kg/m 3 . Gravity data from Jiang and Yu (2005). deformation provides the starting geometry for later Cenozoic deformation (see Burchfiel et al, 1995).…”
Section: Longmen Shanmentioning
confidence: 99%
“…However, the formation and uplift of the Tibetan plateau chiefly resulted in the formation and evolution of the southwestern segment of the basin-mountain system Meng et al, 2006;Hubbard and Shaw, 2009). It has been suggested that the lithosphere strength and the shape of the western margin of the Yangtze plate are the basic controlling attributes of the formation and evolution of the system (Jiang and Jin, 2005).…”
Section: Categorymentioning
confidence: 99%
“…Therefore, a simple one-dimensional crustal model is not appropriate for this area, because large residuals and bias of the velocity structure inversion could be introduced. The Moho discontinuities ( Figure 3) were inverted using the harmonious series method with Bouguer gravity data [17][18][19]. In the initial model, the Moho discontinuities are represented by a linearly continu- ous transition layer.…”
Section: Initial Modelmentioning
confidence: 99%